Mesothelial to mesenchyme transition as a major developmental and pathological player in trunk organs and their cavities. (December 2018) - Koopmans, Tim; Rinkevich, Yuval
Abstract The internal organs embedded in the cavities are lined by an epithelial monolayer termed the mesothelium. The mesothelium is increasingly implicated in driving various internal organ pathologies, as many of the normal embryonic developmental pathways acting in mesothelial cells, such as those regulating epithelial-to-mesenchymal transition, also drive disease progression in adult life. Here, we summarize observations from different animal models and organ systems that collectively point toward a central role of epithelial-to-mesenchymal transition in driving tissue fibrosis, acute scarring, and cancer metastasis. Thus, drugs targeting pathways of mesothelium's transition may have broad therapeutic benefits in patients suffering from these diseases. Tim Koopmans and Yuval Rinkevich review recent findings linking the mesothelium's embryonic programs that drive epithelial-to-mesenchyme transition with adult pathologies, such as fibrosis, acute scarring, and cancer metastasis. They highlight new avenues for drug development that would target pathways of the mesothelium's mesenchymal transition.